Novel polyhydroxyalkanoate bead-based vaccines against Pseudomonas aeruginosa infection : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biological Sciences at Massey University, Palmerston North, New Zealand - Gonzaga, Zennia Jean (Massey University, 2018)
Pseudomonas aeruginosa infections are increasingly problematic due to their multiple antibiotic resistances. To date, there is no commercial vaccine against P. aeruginosa infection. This study used polyhydroxyalkanoate (PHA) beads as a delivery platform for selected P. aeruginosa antigens to produce novel particulate vaccines against P. aeruginosa. Genetic engineering was used to modify the PHA synthase (PhaC), the enzyme that catalyses PHA bead formation, to produce functionalised PHA beads displaying the antigens. The highly conserved PopB antigen, recently revealed as an effective stimulator of Th17 immunity was displayed on the bead surface together with and without the previously selected antigens Ag (epitopes derived from outer membrane proteins OprI, OprF and AlgE). The PHA beads were produced in two production strains: (1) the pathogen P. aeruginosa itself, with the benefit of co-purifying host cell proteins (HCPs) expanding the antigen repertoire that could boost the immune response, and (2) E. coli strain ClearColiTM, a defined mutant incapable of lipopolysaccharide synthesis enabling production of endotoxin free PHA beads. Vaccination of mice with antigen-coated PHA beads (only PopB or with additional Ag) showed increased production of IL-17, a reflection of induction of a Th17 immunity. Furthermore, Th1 and Th2 mediated immunity were detected from the IgG analysis of the immunised mice with the PHA bead vaccines. Significant enhancement of Th1 immune response using the PHA bead platform was observed compared to the antigen-only counterparts. Challenge of immunised mice with pathogenic P. aeruginosa showed that PopB-displaying PHA beads from P. aeruginosa and Ag-displaying PHA beads from E. coli induced partially protective immunity. The promising PHA bead candidate vaccines can be conjugated with other antigens such as the exopolysaccharide Psl for induction of improved immune response towards protective immunity. Exopolysaccharide Psl is a mannose rich polymer produced by P. aeruginosa in both mucoid and nonmucoid phenotypes. Psl has been revealed to play an essential role in P. aeruginosa pathogenicity such as biofilm formation. Previous studies had provided evidence that CdrA binds directly to Psl, functioning as a Psl cross-linker and possibly tethering Psl to the cell surface. Psl is commercially not available, hence the aim of this study was to develop a Psl production strain. This study created a cdrA knockout mutant that produces free Psl which may be a potential vaccine antigen against P. aeruginosa infections. An isogenic knockout of cdrA was obtained by homologous recombination and this mutant overproduced Psl released from the cell surface. In future studies, this strain will be used to produce Psl to serve as antigen in vaccine formulations.
Figures 1, 2, 3, 4, 5 & 6 and Table 1 have been removed for copyright reasons, but may be accessed via their source listed in the References.
Keywords: Vaccines|xBiotechnology; Pseudomonas aeruginosa infections; Antigens